2013
DOI: 10.1055/s-0033-1350647
|View full text |Cite
|
Sign up to set email alerts
|

2-(2-Phenylethyl)chromone Derivatives in Chinese Agarwood “Qi-Nan” from Aquilaria sinensis

Abstract: Five new 2-(2-phenylethyl)chromone derivatives, qinanones A-E (1-5), together with eight known 2-(2-phenylethyl)chromone derivatives (6-13), were isolated from the Et2O extract of high-quality Chinese agarwood "Qi-Nan" originating from Aquilaria sinensis. The structures of the new 2-(2-phenylethyl)chromones were elucidated by spectroscopic techniques (UV, IR, 1D and 2D NMR) and MS analyses. In the bioassay for acetylcholinesterase inhibitors, compounds 1-6, 10, and 12 exhibited weak inhibitory activities (inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…Qinanone G (1) was obtained as colorless needle crystals, and its molecular formula being C 19 Table 1), indicated that one methine was attached by an oxymethine group in compound 2. The oxymethine group was located at C-7 0 by the HMBC correlations from the oxymethine proton (d H 5.08) to C-2 0 and C-6 0 (d C 128.2) ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qinanone G (1) was obtained as colorless needle crystals, and its molecular formula being C 19 Table 1), indicated that one methine was attached by an oxymethine group in compound 2. The oxymethine group was located at C-7 0 by the HMBC correlations from the oxymethine proton (d H 5.08) to C-2 0 and C-6 0 (d C 128.2) ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, as a continuous and important part of our work on agarwood, the investigation on one sort of high quality Chinese agarwood 'Qi-Nan', so called 'Lv Qi-Nan' (also called Ryokuyu in Japanese [5]), originating from Aquilaria sinensis (Lour.) Gilg, has led to the isolation of 2-(2-phenylethyl)chromone derivatives qinanones A -F [19]. Futher fractionation of the same material resulted in the isolation of a new 2-(2-phenylethyl) chromone derivative (1), namely qinanone G, and four known 2-(2-phenylethyl) chromones (2 -5) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the reported studies focused on A. sinensis. Sesquiterpenoids and 2-(2-phenylethyl)chromone derivatives (tested at 50 µg/mL) inhibited 12.3 to 61.9 % of acetylcholinesterase activity compared with tacrine (positive control), which inhibited approximately 70 % of the activity at 0.08 µg/mL (Li et al, 2015b;Yang et al, 2014a;Yang et al, 2014b). Neopetasane (1), an eremophilane sesquiterpene, showed the strongest inhibition (61.9 %) (Yang et al, 2014a).…”
Section: Compounds Isolated From Resinous and Healthy Woodmentioning
confidence: 99%
“…S-Acetylthiocholine iodide, 5,5 -dithio-bis-(2-nitrobenzoic) acid (DTNB), Ellman's reagent and AChE were purchased from Sigma Chemical company (St. Louis, MO, USA). The specific experimental procedures were the same as those described previously [12].…”
Section: Bioassay Of Ache Inhibitory Activitymentioning
confidence: 99%